จิตตปัญญาศึกษานวัตกรรมพัฒนาคุณลักษณะคนไทยที่พึงประสงค์ให้แก่แผ่นดิน ตอนที่ 3 : ศาสตร์แห่งนพลักษณ์ (Enneagram) - สัตโยภาส, สนิท (Ganesha Journal, 2012)
[บทคัดย่อภาษาไทยไม่สมบูรณ์] Enneagram is the study that emphasize on the understandings of the 9 types of human from their views, interests and their basic needs. It is also the tool to help understanding oneself and people around them. Moreover, it helps cultivate deeply caring and kindheartedness both to oneself and the others since the studies is based on the true understandings on their own and the others. The self-examined activities and the study of the main concreted 9 characteristics of the humans are taught and practiced among the groups who study this subject, in order that they can learn from the real life surroundings.